Planeación ambiental participativa: de la teoría a la práctica en San Cristóbal de Las Casas, Chiapas - Aguiluz Casas, Grelsvia A.; Vásquez Sánchez, Miguel A.; Molina Rosales, Dolores O.; Saldívar Moreno, Antonio (El Colegio de México A.C., 2001)
The theory of environmental planning postulates that social participation is an indispensable requirement for reducing the conflicts derived from the confrontation of various interests. In this respect, the aim of this study has been to provide a conceptual reconstruction of the participatory approach of three sectors (government, academic and civil) that converge in an environmental planning process, promoted by the Interdisciplinary and Civic Environmental Collective (CICE) in San Cristobal de Las Casas, Chiapas. The comparative information was obtained from participatory observation in twenty-four group sessions (held between February and September 1998) and twenty semi-structured interviews; twelve with key informants from the group and eight with representatives from social organizations. The results show that the three sectors acknowledge the fact that social participation is required to produce changes on the local scale; however, there is no consensus on its meaning. There is a similar lack of clarity concerning concepts such as "environmental problems" and "civil society" as well as methodologies and communication mechanisms, management and social participation in local spheres which hampers the planning process. This analysis recognizes the need to advance in common conceptual proposals that will make it possible to go beyond social participation processes towards the construction of viable development.